Determinants and prevalence of childhood overweight and obesity in pre-school children of Duwakot, Bhaktapur - Kharel, Sushil; Raut, Binod (Journal of Physiological Society of Nepal, 2020)
Introduction: Adverse dietary patterns and sedentary lifestyle predispose to overweight-related non-communicable diseases both in children and in adults. In Nepal, childhood overweight is one rapidly growing public health concern in the urban areas. Many studies have focused on the relationship between overweight and its associated risk factors. We aimed to find the prevalence of overweight including obesity and its determinants in pre-school children aged 2 to 4 years in Duwakot community, Bhaktapur.. Materials and methods: In a community-based cross-sectional survey, total 122 pre-school children both males and females of age between 2-4 years were studied. A structured questionnaire was used to obtain information on socioeconomic characteristics and life style factors of children. WHO Anthro Software Version 3.2.2 was used for analyzing anthropometric parameters of the children. Results: The prevalence of overweight in pre-school children was 13.9%. The prevalence of overweight including obesity was significantly higher among male children (17.7%) than female children (10%). The study revealed that overweight was significantly associated with sedentary lifestyles of children and higher socio-economic status of the family. Conclusions: The magnitude of overweight is big and increasing rapidly in Nepal due to sedentary lifestyles and improper dietary habits among pre-school children, especially in the cities. Proper interventions should be implemented to minimize the overweight among pre-school children in order to avoid further health ailments in future.